Is Female Wellness Affected When Men Blame Them for Erectile Dysfunction?. Issue 3 (29th May 2021) - Dubin, Justin M.; Wyant, W. Austin; Balaji, Navin C.; Efimenko, Iakov V.; Rainer, Quinn C.; Mora, Belen; Paz, Lisa; Winter, Ashley G.; Ramasamy, Ranjith
Abstract: Introduction: Several studies have investigated the association between erectile dysfunction (ED), its treatment, and female sexual dysfunction, but the impact of males blaming their female partners for their ED remains unknown. Aims: To investigate whether women who are blamed by their male partners for their ED experience worse overall sexual function and satisfaction. Methods: We performed a global, cross-sectional web-based survey to investigate female perceptions of ED. We distributed the 30-item survey via email, Reddit, Amazon Mechanical Turk, and Facebook. Women 18 years of age or older were eligible to participate and answered questions based on a 5-point Likert scale. Women were grouped by ages 18-29, 30-39, and 40 and older. Main Outcome Measures: The survey collected data that included general demographics and questions regarding experiencing male blame for ED and its relationship with each subject's sexual health and wellness. Results: A total of 13, 617 females participated in the survey. Of the women surveyed, 79% have experienced their partner losing their erection during sexual activity and approximately 1 out of 7 women (14.7%) had experienced being blamed by their partner for loss of their erection. Women who were blamed for their partner's ED were more likely to end the sexual encounter, were less sexually satisfied, and were more likely to end relationships due to their partner's ED. Conclusion: Approximately 1 out of 7 women have experienced male blame for their partner's ED which is associated with negative impacts on female mental health, sexual satisfaction and the success of the overall partnership. Because of its widespread impact on female wellness, male blame should be considered during evaluation of female sexual history and men must be educated on the significant impact their reactions during intimacy have on their female partners and their relationships as a whole.